1997
DOI: 10.1021/bk-1997-0679.ch017
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Electron Transfer Dynamics of Photosensitized Zinc Oxide Nanoclusters

Abstract: We have prepared and characterized photosensitized zinc oxide (ZnO) nanoclusters, dispersed in methanol, using carboxylated coumarin dyes for surface adsorption. Femtosecond time-resolved emission spectroscopy allows us to measure the photo-induced charge carrier injection rate constant from the adsorbed photosensitizer to the n-type semiconductor nanocluster. These results are compared with other photosensitized semiconductors. IntroductionPhotosensitized nanoclusters of wide bandgap n-type semiconductors are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(84 citation statements)
references
References 0 publications
3
81
0
Order By: Relevance
“…This system has been investigated experimentally by a number of groups. 3,5,6,13,81 Recently, we have studied the electronic injection dynamics as well as the associated nuclear wave packet dynamics in this system employing a semiempirical Newns model. 41 Here, we apply the first-principles model outlined above.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…This system has been investigated experimentally by a number of groups. 3,5,6,13,81 Recently, we have studied the electronic injection dynamics as well as the associated nuclear wave packet dynamics in this system employing a semiempirical Newns model. 41 Here, we apply the first-principles model outlined above.…”
Section: Theorymentioning
confidence: 99%
“…3,5,6,13,81 This discrepancy can have a variety of reasons. As discussed above, the electron-injection dynamics are not a single-exponential decay but also exhibit a slower injection component as well as oscillatory structures, which may result effectively in an overall longer injection time.…”
Section: Theorymentioning
confidence: 99%
“…7,[32][33][34][35][36][37] Another application of the 7-aminocoumarins, especially the 3-carboxylic acid derivatives, has been as photosensitizing dyes for wide band gap semiconductors such as TiO 2 and ZnO. 24,[38][39][40][41][42] Excited-state proton-transfer reactions have also been widely studied using 7-aminocoumarins. [43][44][45][46][47][48] We have recently published a theoretical study of coumarins 151 and 120.…”
Section: Introductionmentioning
confidence: 99%
“…coumarin 343 (C343) (Scheme 1), are recognized as good organic dye photosensitizers, injecting electrons effectively into the conduction band of semiconductors. 10,11 For example, Murakoshi et al observed an ultrafast electron injection ( < 20 fs) from C343 into the conduction band of TiO 2 . 11 The h values of nanocrystalline semiconductor solar cells using conventional coumarin dyes such as C343 as the photosensitizer is, however, much lower than that of solar cells sensitized by Ru complex photosensitizers because of the narrow absorption area in the visible region.…”
mentioning
confidence: 99%